Post-traumatic stress disorder in participants of foot-and-mouth disease epidemic control in Miyazaki, Japan, in 2010 - Hibi, J.; Kurosawa, A.; Watanabe, T.; Kadowaki, H.; Watari, M.; Makita, K. (Japanese Society of Veterinary Science, 2015)
Foot-and-mouth disease (FMD) occurred in Miyazaki, Japan, in 2010, and 290,000 animals were culled. This paper describes the mental distress of the volunteers who had been dispatched to Miyazaki for disease control two years after the epidemic. It also assesses risk factors for post-traumatic stress disorder (PTSD). A participatory appraisal and self-administered questionnaire survey were conducted in 2012 for those who were dispatched to Miyazaki in 2010. The Impact of Event Scale-Revised (IES-R) was used as an indicator of PTSD, and univariate and multivariable analyses were performed. Of the 875 respondents, 1.3% had higher IES-R scores than the cut-off point (25), which is suggestive of PTSD. Mental stresses during and soon after FMD control and after two years were described. Four risk factors associated with high IES-R scores were found: transporting culled animals (P<0.01), stress during FMD control (P<0.01) and at the time of the survey (P<0.01), and lack of someone to talk to about FMD-associated stress at the time of the survey (P<0.01). Veterinarians, livestock technicians and clerical officers involved in FMD control still suffer from mental stress two years later. Public services should provide an opportunity for them to consult with mental health specialists. These findings should be used to better prepare workers who deal with infectious diseases of animals, especially when they must be culled. The establishment of a collaborative framework between veterinary and mental health services is recommended.